Tourism and biodiversity loss: implications for business sustainability - Habibullah, Muzafar Shah; Din, Badariah; Choo, Wei Chong; Radam, Alias (Elsevier, 2016)
The purpose of this study is to investigates the impact of tourism on biodiversity loss in a sample of 141 countries. In the analysis, we measure tourism using the numbers of international tourist arrivals, while biodiversity loss is proxy using the numbers of threatened species – birds, fishes, mammals and plants. We also include GDP per capita, population growth, protected areas, and crop production, which act as the control variables. We find that using robust standard error estimator the number of international tourist arrivals, population growth rate, protected areas and crop production increases the numbers of threatened species, while GDP per capita reduces the numbers of threatened species. One policy implication of this study is that since businesses in the tourism industry depend on the very existence of biodiversity, then biodiversity conservation should become the essential factor for business sustainability.